Comparative analysis of organisational forms of students’ learning activities in university physical education (using the elective discipline “badminton” as an example) - Barchukova, G.V.; Manman, Liu (Theory and Practice of Physical Culture, 2026)
Objective of the study is to conduct a comparative analysis of organisational forms of learning activities – frontal, group, flow-based, pair, and individual-independent – and to systematise the organisational-methodological conditions ensuring the implementation of physical education and health-enhancing activities in higher education institutions. Methods and structure of the study. Observations were conducted during badminton training sessions over 15-minute intervals, applying various organisational forms of learning activities in elective “Badminton” classes with first-year students at Zhengzhou University, Henan Province, China. Results and conclusions. It was established that frontal, group, flow-based, pair, and individual-independent forms create fundamentally different conditions for the implementation of health-enhancing and pedagogical objectives within the “Physical Education” discipline. This provides a methodological basis for instructors to select organisational forms depending on students’ fitness levels, material and technical resources, and educational objectives of the university.